2020
DOI: 10.3847/1538-4357/ab8870
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Geometry and Composition Variation in Slow Solar Winds: The Case of Sulfur

Abstract: We present an examination of the first ionization potential (FIP) fractionation scenario, invoking the ponderomotive force in the chromosphere and its implications for the source(s) of slow-speed solar winds by using observations from The Advanced Composition Explorer (ACE). Following a recent conjecture that the abundance enhancements of intermediate FIP elements, S, P, and C, in slow solar winds can be explained by the release of plasma fractionated on open fields, though from regions of stronger magnetic fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…213 Å,Fe IX 188.497 Å,Fe X 184.536 Å,Fe XI 188.216 Å,Fe XI 188.299 Å,Fe XII 195.119 Å,Fe XII 203.72 Å,Fe XIII 202.044 Å,Fe XIII 203.826 Å,Fe XIV 264.787 Å,Fe XV 284.16 Å,and Fe XVI 262.984 Å. 3 Si X 258.37 Å and S X 264.22 Å. studies, it lies close to the boundary between low and high FIP elements, and it has been suggested that it can exhibit both low and high FIP behaviour (Reames 2018;Kuroda & Laming 2020). Ideally another element with a higher FIP would be used, but emission lines from other high FIP elements are challenging to measure with Hinode/EIS (Feldman et al 2009).…”
Section: Coronal Compositionmentioning
confidence: 94%
“…213 Å,Fe IX 188.497 Å,Fe X 184.536 Å,Fe XI 188.216 Å,Fe XI 188.299 Å,Fe XII 195.119 Å,Fe XII 203.72 Å,Fe XIII 202.044 Å,Fe XIII 203.826 Å,Fe XIV 264.787 Å,Fe XV 284.16 Å,and Fe XVI 262.984 Å. 3 Si X 258.37 Å and S X 264.22 Å. studies, it lies close to the boundary between low and high FIP elements, and it has been suggested that it can exhibit both low and high FIP behaviour (Reames 2018;Kuroda & Laming 2020). Ideally another element with a higher FIP would be used, but emission lines from other high FIP elements are challenging to measure with Hinode/EIS (Feldman et al 2009).…”
Section: Coronal Compositionmentioning
confidence: 94%
“…In the open field, S behaves more like a low FIP element, while in closed field it more closely resembles a high FIP element. The reasons for this have been previously discussed (Laming et al, 2019;Kuroda and Laming, 2020) (Reames, 2018). It is curious then that CO1 appears to exhibit abundances more appropriate to a closed loop than to open field (see Fig.…”
Section: Modelling the Fip Biasmentioning
confidence: 89%
“…The wave angular frequency is taken to be the resonant frequency for each loop, assuming that the Alfvén waves have a coronal origin. For each model we give two fractionations, one arising solely from the ponderomotive force as would be revealed by spectroscopy of emissions from close to the solar surface, and a second incorporating also the effects on abundances of the conservation of the first adiabatic invariant in the expanding magnetic field lines (Laming et al, 2017(Laming et al, , 2019Kuroda and Laming, 2020), as would be detected in-situ. We assume (as before) that the plasma becomes collisionless at a density of ∼ 10 6 cm −3 , which in this open field region occurs at a radius of about 2.5 R .…”
Section: Modelling the Fip Biasmentioning
confidence: 99%
“…Sulfur lies on the boundary between low-and high-FIP elements and shows variable behavior that is sometimes consistent with one group or the other. In some theoretical models this depends on the open or closed topology of the magnetic field (Laming et al 2019;Kuroda & Laming 2020), making it a useful diagnostic regardless (Brooks & Yardley 2021b).…”
Section: Atomic Data and Analysis Methodsmentioning
confidence: 99%